20-Year Follow-up Study of Celiac Patients Identified in a Mass School Screening: Compliance to Gluten-Free Diet and Autoimmunity. Issue 1 (9th January 2022) - Cozzi, Giorgio; Gabbana, Eleonora; Zanchi, Chiara; Giudici, Fabiola; De Leo, Luigina; Ziberna, Fabiana; Bramuzzo, Matteo; Di Leo, Grazia; Not, Tarcisio
ABSTRACT: Objectives: To investigate the compliance to the gluten-free diet in a cohort of adult celiac patients 20 years after the diagnosis, received in childhood through a mass screening. Methods: This is an observational historic cohort follow-up study. It was carried out at the Institute for Maternal and Child Health IRCCS Burlo Garofolo, Trieste, Italy. Two matched cohorts of adult celiac patients, diagnosed in childhood through a mass screening or for symptoms were enrolled. Adherence to the gluten free-diet and development of autoimmune diseases were investigated through a questionnaire administrated in the course of a phone interview. The primary study outcome was the adherence to the gluten-free diet, measured through the Biagi questionnaire, in the two cohorts of celiac patients. Results: We contacted 25 patients (mean age 28 years, 19 females) diagnosed with screening and 34 patients (mean age 25 years, 26 females) diagnosed in the same period for symptoms. After 20 years, in the cohort diagnosed with screening and in the cohort diagnosed for symptoms the adherence to the gluten-free diet was optimal in 14 (56%) and 26 (81%), improvable in 5 (20%) and 3 (9%), inadequate in 6 (24%) and 3 (9%), respectively. In the two cohorts, four patients (16%) and six patients (18%) developed other autoimmune diseases. Conclusions: Twenty years after the diagnosis, near half of the patients diagnosed in a mass screening, does not have an optimal adherence to the gluten-free diet and a remarkable proportion of them have developed another autoimmune disease.